The looming tower : Al-Qaeda and the road to 9/11 - Wright, Lawrence, 1947- (New York : Vintage Books, 2006)
Explores both the American and Arab sides of the September 11th terrorist attacks in an account of the people, ideas, events, and intelligence failures that led to the tragedies.
The martyr -- The sporting club -- The founder -- Change -- The miracles -- The base -- Return of the hero -- Paradise -- The Silicon Valley -- Paradise lost -- The prince of darkness -- The boy spies -- Hijira -- Going operational -- Bread and water -- "Now it begins" -- The new millennium -- Boom -- The big wedding -- Revelations.
Includes bibliographical references (p. 489-500) and index.
Keywords: September 11 Terrorist Attacks, 2001.; Qaida (Organization); Terrorism -- Government policy -- United States; Intelligence service -- United States; September 11 terrorist attacks, 2001.; Qaida (Organization); Terrorism -- Government policy -- United States; Intelligence service -- United States; Terrorisme -- 2